Appealing to the Crowd: Motivation Message Framing and Crowdsourcing Performance in Retail Operations. Issue 9 (28th April 2021) - Ta, Ha; Esper, Terry L.; Tokar, Travis
Abstract : For the execution of many supply chain operations tasks, firms are increasingly engaging in crowdsourcing—the act of dynamically delegating work via digital channels to for‐hire individuals intermittently available in the marketplace (also called "the crowd"). The success of this practice hinges on the ability to efficiently attract workers who produce quality work from among the crowd. We draw on the foundations of Self‐Determination Theory and the heuristic‐systematic model to examine the ways that variations in messages presented to crowdsourced agents can serve as a mechanism to enhance participation and associated performance outcomes. Data from a field experiment involving a retail inventory audit task reveal that messages appealing to the crowd's consumer identity, as opposed to crowdsourcing platform identification or firm identification, generally lead to superior performance outcomes, particularly shorter reservation time, higher task quality approval, and post‐task satisfaction. However, these effects are contingent on the valence of the message frame and the nature of the task. These findings shed light on elements critical to the successful utilization of this new type of crowdsourced "employment" in supply chain and operations tasks and suggest the careful crafting of crowdsourced task messages as a low‐cost way for managers to improve task performance outcomes.